Monetary policy announcements of the reserve bank of India and the role of information shock - Patnaik, Anuradha (Economic and Political Weekly)
Inflation-targeting central banks supplement their monetary policy announcements with communication in the form of speeches and publication of text documents. The markets react to the surprise component of the rate action and the communication by the central bank. Thus, the monetary surprise derived from the reaction of markets, following a policy announcement, is agglutinated with the central bank information. The present paper attempts to identify and examine the efficacy of such an information shock in influencing the inflation expectations of households, interest rate expectations of agents, output and inflation.- Reproduced